KEBIASAAN MENCUCI TANGAN DENGAN KEJADIAN DIARE PADA ANAK SEKOLAH DASAR NEGERI KOTA WAINGAPU KABUPATEN SUMBA TIMUR - KODY, MARTHA METI; LANDI, MELKISEDEK (Poltekkes Kemenkes Kupang, 2016)
Introduction: based on the pattern of the cause of death of all age, diarrhea is the leading cause of death of the 13th ranked by the proportion of the deaths of 3.5%. Diarrhea is the leading cause of death number 3 after Tuberculosis and Pneumonia. East Sumba Regency has a prevalence of diarrhea clinical > 9%. The purpose of the study to find out the relationship between the habit of washing hands with SOAP to use on students with variable incidence of diarrhea on elementary school students of the country town of waingapu subdistrict of East Sumba Regency. Methods: this research is quantitative research Types, with a descriptive correlation design, which used a crosssectional approach. Results: 26 people or 13% suffer from diarrhea in the last 3 months. Conclusions: knowledge of elementary school children in the hand washing was heavily influenced by the teachers at the school, Elementary school children enough in getting used to the district town of Waingapu 13% of respondents suffer from diarrhea in the last 3 months. there is a significant relationship between hand washing with diarrhea in children of primary school.